From the Mountain, From the Valley : New and Collected Poems - Still, James, 1906-2001 (Book collections on Project MUSE., 2001)
James Still first achieved national recognition in the 1930s as a poet. Although he is better known today as a writer of fiction, it is his poetry that many of his essential images, such as the ""mighty river of earth, "" first found expression. Yet much of his poetry remains out of print or difficult to find. From the Mountain, From the Valley collects all of Still's poems, including several never before published, and corrects editorial mistakes that crept into previous collections. The poems are presented in chronological order, allowing the reader to trace the evolution of Still's.